Interactions of Art and Art Pedagogy : Theory and Practice - Klāsone, Inta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article raises the issue of the link between art and its variet expressions of form with pedegaogy of art. A number of important directions of scientific research in art pedagogy are highlighted on the basis of the scientific knowledge base in the world and Latvian Education Area, guidelines of National Strategic Guidance, trends in art and art education, and summary of survey data. Object of the research is the interaction process between art and art education for improvement of pedagogical work performance; the objective of the study is: to identify major research issues in the process of interaction of art and art pedagogy in today's context, providing the basis for a balanced, cognitive, emotional, aesthetic and social development of a personality.